Influência de fontes de nitrogênio no consumo e digestibilidade aparente total e parcial de novilhos alimentados com cana- deaçúcar - Da Silveira, Roselene Nunes [UNESP]; Berchielli, Telma Teresinha [UNESP]; Canesin, Roberta Carrilho [UNESP]; Messana, Juliana Duarte [UNESP]; Reis, Ricardo Andrade [UNESP]; Resende, Kleber Tomás de [UNESP] (Universidade Estadual de Maringa, 2009)
The objective of this work was to evaluate the effect of nitrogen sources, using sugarcane supplemented with urea, corn gluten meal-60 or soybean meal. It was evaluated Intake, total and partial apparent digestibility were evaluated using four rumen and duodenal cannulated crossbred steers. The treatments were evaluated in a 4 × 4 Latin square design. The total feces were collected to determine the apparent digestibility on the total intestinal tract. The indigestible acid detergent fiber (iADF) was used as marker of duodenal flux to determine ruminal and intestinal digestibility and dry matter daily flux. The DM, OM, CP, EE, DE, NDF, ADF and TC intakes and digestibility rates were influenced by nitrogen sources, and lower intake was observed in animals fed exclusively with cane sugar compared to animals fed the other experimental diets. Meanwhile the sources of nitrogen did not affect the total digestible nutrients (TDN) values. The RDP sources did not affect the total, ruminal, and intestinal nutrients apparent digestibility. However, the total, ruminal, and intestinal dry matter, and protein apparent digestibility were affected by the RDP sources.
Effects of nitrogen sources in the intake, total and partial digestibility of steers feeding on sugarcane
Keywords: Acid detergent insoluble fiber; Corn gluten meal-60; Intestinal digestibility; Ruminal digestibility; Soybean meal; Urea; Animalia; Glycine max; Zea mays